Determination of pedestrian’s personal space in mass religious gatherings - A case study of Kumbh Mela - P M, Aparna; Sobhana, Karthika; Verma, Ashish (Collective Dynamics, 2020)
Personal space can be defined as the physical distance between two individuals in a social environment. It varies from person to person depending on culture and context and there are significant individual differences too. Studying personal space includes the ability to recognize the various zones of involvement and the activities, relationships, and emotions associated with each zone. This paper tries to formulate and define personal space in high density crowd situations in Kumbh Mela, one of the world’s largest mass religious gatherings. Video data of pilgrims taking part in the Panchkroshi Yatra, a religious walkathon which is a part of KumbhMela, is used for the analysis of factors affecting personal space. To identify the thresholds of personal space, walking speed of individuals, gender, presence of luggage and the number of males and females surrounding an individual have been considered. It is found that the average speed of the individual, the group size,and the gender ratio of group members have a significant effect on the personal space of an individual. Also, it is observed that the personal space follows an asymmetrical pattern rather than a symmetrical pattern.